Causes and complications of osteosynthesis of diaphyseal fractures in the long bones in the dog - ΔΕΣΙΡΗΣ Α.; ΠΑΠΑΔΟΠΟΥΛΟΣ Φ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The causes and complications in 55 cases of osteosynthesis in the 4 long bones in the dog are described. As proven by practice, unsuccessful immobilisation constritutes the commonest cause of complications in the osteosynthesis, followed by the choice of unsuitable osteosynthetic material and detriment of this material.